Alcool e radicais livres. Algumas consequências: síntese proteica, disendocrinias, imunidade. Importância do stress. - Manso, C F (Acta Médica Portuguesa, 1997)
Ethanol is a powerful generator of oxygen free radicals, when metabolized in the liver or in other organs. Isoenzyme 2E1 of cytochrome P450 and aldehyde oxidase are the main mechanisms for the generation of these radicals. A consequence of free radical generation is a decrease in protein synthesis. As a result we have endocrine and immunity alterations. The paper ords with a brief discussion of stress associated to alcoholism.